Fostering Mitigation Awareness in Disaster Communication: A Study of KPH Brang Beh, Sumbawa Regency - Anshori, M. Syukron; HR, Trian Nugroho; Al Mujib, Ihwan Huda (Journal of Language, Communication, and Tourism, 2024)
This study aims to explore the role of the Forest Management Unit Brang Beh in managing natural resources within its jurisdiction, and to identify challenges in community awareness and readiness regarding disaster risk mitigation. Utilizing a qualitative research approach with a case study method, this study reveals a significant gap in public understanding of disaster risks and mitigation strategies, primarily influenced by insufficient communication and dissemination of adequate information. Research findings indicate that effective communication plays a crucial role in enhancing public awareness and participation in disaster risk mitigation. Communication challenges, such as limited access to official information platforms and inadequate disaster mitigation education, underscore the importance of adopting a more strategic and inclusive communication approach by KPH Brang Beh.